Dolmabahçe Sarayı arşiv koleksiyonunda Hazine-i Hassa defterlerinin yeri ve bir katalog - Demiray, Gökçe (My University, 2010)
Dolmabahçe Sarayı Hazine-i Hassa Arşivi, saray arşivi olma özelliğinin yanı sıra, Hazine-i Hassa Nezareti olarak adlandırılan müesseseye ait kalemlerde ve hazineye bağlı olarak çalışan dairelerde tutulmuş olan defter ve evraklardan oluşmaktadır. Bu çalışmada, Hazine-i Hassa Nezareti'nin teşkilât ve idâresi hakkında bilgi verilmiş, Hazine-i Hassa'ya ait ilk 20 yıl dikkate alınarak, Başbakanlık Osmanlı Arşivi defter katalogları standartlarına göre bir katalog hazırlanmıştır. Hazırlanan örnek katalogda, Hazine-i Hassa'ya ait olan Karhane İdaresi, Mefruşat Anbarı, Ebniye Anbarı, Istabl-ı Âmire, Muhasebe Kalemi gibi birimlerde oluşturulmuş farklı defter ve form türleri hakkında malûmat verilmektedir.

Beside serving as the palace archive, the Ottoman Imperial Treasury Department of the Dolmabahce Palace consisted of registries and documents related to the units of the institution called the Ottoman Imperial Treasury Administration and to the departments under the control of the Treasury. In this study, the information has been given on the organization and administration of the Ottoman Imperial Treasury Administration and a catalogue has been prepared in line with the registry catalogue standards of the Ottoman Archive of the Prime Ministry covering first 20 years of the Ottoman Imperial Treasury Department. The example catalogue gives information about different registries and form types available in units such as Karhane İdaresi which supplied the Imperial Palace with ice and snow in summer months, the furnishing store (Mefruşat Anbarı), the administration controlling the construction and maintenance of the buildings of the Empire (Ebniye Anbarı), the Imperial stables (Istabl-ı Âmire) and the accounting department under the control of the Imperial Treasury (Muhasebe Kalemi).
Keywords: Arşivcilik; Arşivler; Belge Yönetimi